Pulse electric field effect on cervical cancer cell: a plant based anti-cancer study - Ganeson, Suhassni (2018)
Cancer is listed in top ten global causes of death in 2016. The percentage of cancer incidence and mortality are steadily rising over the year. This necessitates alternate anti-cancer treatment as the conventional treatment have resulted in high number of long- term survivors who are left to deal with the aftereffect of their therapy. Drug delivery is a challenging aspect in medical community as the plasma membrane is non-permeable to external molecules. From this context, a study was proposed to use of natural plant extract Artocarpus altilis which will be uploaded into cervical cancer cell with the aid of electrical pulses or electroporation technique to investigate on the anti-cancer mechanism. Electroporation parameters utilized in this study ranging from 200V/cm, 400V/cm, 600V/cm, 800V/cm, 1000V/cm of pulse amplitude, while pulse duration ranging from 100μs, 500μs, 1ms, 5ms and 10ms with single pulse. Three parts of artocarpus altilis tested in this research study which is the peel, pulp and whole fruit. The concentration of all three parts which were tested on cervical cancer cell ranged from 10μg/ml, 20μg/ml, 30μg/ml, 40 μg/ml, and 50μg/ml with methanol as the solvent. It is found that pulse electric field increased the cell spreading up to 129.8% with 600V/cm of pulse amplitude, which stimulates to the highest cell length percentage. Apart from that, cell viability found to be decrease with an increase in pulse amplitude and pulse duration. 600V/cm of pulse amplitude and 10ms of pulse duration stimulates highest cell viability with 53.3% as compared to control group (without treatment). Cell viability of cervical cancer cell measured when cell subjected to electrical field alone, extract alone and both electrical field and extract and the result of the study revealed that lowest cell viability stimulated by the combination of electrical pulse and extract up to 28% of cell viability. Thus the outcome of this research revealed new targets and electrochemical pathways for cervical cancer treatment while with the discovery health of patients will be maintained and there will be an improvement in general life expectancy.